Plasma Metabolomics Reveals Steroidal Alkaloids as Novel Biomarkers of Tomato Intake in Mice. Issue 12 (4th October 2017) - Cichon, Morgan J.; Riedl, Ken M.; Wan, Lei; Thomas‐Ahner, Jennifer M.; Francis, David M.; Clinton, Steven K.; Schwartz, Steven J.
Abstract : Scope: Diets rich in tomato products are associated with a reduced risk of various chronic disease processes. The carotenoid lycopene is most intensely studied as the bioactive mediating health effects, yet tomatoes contain an array of phytochemicals. An untargeted metabolomics study is conducted on blood plasma to identify novel markers of tomato consumption absorbed from the diet and released into the bloodstream in mice. Methods and results: Male mice are fed a control AIN‐93G diet or the same diet supplemented with 0.25 % lycopene beadlets, or 10 % freeze‐dried red tomato, tangerine tomato, or low‐carotenoid tomato for 4 weeks. Untargeted UHPLC‐QTOF‐MS data acquisition and differential analysis of plasma metabolites reveals several structurally related deglycosylated tomato steroidal alkaloids, including tomatidine and hydroxylated/desaturated derivatives, in plasma after the consumption of all three tomato varieties. Additionally, plasma metabolite profiles reflect glycoalkaloid forms found in the tomato diets. Conclusion: Dietary tomato glycoalkaloids are cleaved during digestion to aglycones and further metabolized post‐absorption. Steroidal alkaloids in plasma may serve as novel and specific biomarkers of tomato consumption and represent a class of phytochemical metabolites that could potentially have in vivo bioactivity impacting health and disease processes. Abstract : An untargeted metabolomics approach is employed to determine novel biomarkers of tomato consumption in a polar extract of plasma. Mice are fed a control diet or the same diet supplemented with lycopene beadlets or freeze‐dried red, tangerine, or low carotenoid tomatoes for four weeks. High resolution mass spectrometry metabolomics reveals a series of tomato glycoalkaloid metabolites, including tomatidine, as plasma markers of tomato intake in mice.